TOX as a diagnostic and prognostic marker for mycosis fungoides. Issue 1 (January 2018) - El-Hamd Neinaa, Yomna M.; Sallam, Fersan A.
Abstract : Background: Mycosis fungoides (MF) is the most common primary cutaneous T-cell lymphoma that is characterized by clonal expansion of atypical CD4 + skin-homing T lymphocytes. Thymocyte selection-associated high mobility group-box protein (TOX) is a nuclear transcription factor, highly expressed in the thymus, and plays a critical role in CD4 + T-cell development. Therefore, it is likely that TOX activation may participate in the pathogenesis of MF. Objective: To study the immunohistochemical expression of TOX in MF specimens in comparison with normal control skin specimens to shed light on its possible role in the pathogenesis of MF and to evaluate its efficacy as a possible diagnostic and prognostic marker for MF. Patients and methods: The current study was carried out on 50 patients with different clinical types of MF and 25 normal control skin specimens. They were selected from the Outpatient Clinic of Dermatology and Venereology Department, Tanta University Hospitals. Skin specimens were obtained from each participant and examined routinely by hematoxylin and eosin and immunohistochemically by CD3, CD4, and TOX antibodies. Results: There was a statistically significant increase in TOX immunohistochemical expression in MF specimens in comparison with normal control skin specimens. Statistically significant positive correlations were detected between the intensity of TOX expression in the dermis of MF specimens and the age of the patients, clinical progression of skin lesions, and TNM staging of the disease. In addition, there was a statistically significant positive correlation between the intensity of TOX expression, and the expression of both CD3 and CD4 both in the epidermis and in the dermis of MF specimens. Conclusion: TOX may participate in the pathogenesis of MF. It could be considered a diagnostic and prognostic marker for MF. TOX expression correlates with increased risks of disease progression and a poor prognosis.